Power systems electromagnetic transients simulation - Watson, N. R.; Arrillaga, J. (Stevenage IET, 2003)
The following topics are dealt with:continuous systems; discrete systems; state variable analysis; numerical integrator substitution; root-matching method; transmission lines and cables; transformers; rotating plant; power electronic systems; frequency dependent network equivalents; mixed time-frame simulation; transient simulation; PSCAD/EMTDC program; system identification; difference equations; Matlab code; FORTRAN code; and EMT simulation.
Electronic reproduction.
Keywords: Electric power systems; Transients (Electricity); Electronic books